The Effect of Glatiramer Acetate on Retinal Nerve Fiber Layer Thickness in Patients with Relapsing–Remitting Multiple Sclerosis: A Longitudinal Optical Coherence Tomography Study - Zivadinov, Robert; Tavazzi, Eleonora; Hagemeier, Jesper; Carl, Ellen; Hojnacki, David; Kolb, Channa; Weinstock-Guttman, Bianca (CNS drugs, 2018)
Background Optical coherence tomography (OCT) is a technique that allows for the assessment of retinal nerve fiber layer thickness (RNFLT) and total macular volume (TMV), which reflect neuroaxonal integrity within the retina. As such it has been used in multiple sclerosis (MS) to study neurodegeneration. Glatiramer acetate (GA) is a widely used treatment for MS, which is suggested to have a possible neuroprotective role. Objective The aim of this study was to assess RFNLT and TMV changes in relapsing–remitting MS (RRMS) patients who started treatment with GA and were followed for a 24-month period. Methods A cohort of 60 RRMS patients and 40 healthy controls (HCs) were imaged with OCT at baseline and follow-up. All subjects also underwent clinical and neurological examination. Measurements were compared between the RRMS patients and HCs as well as between optic neuritis (ON)-affected and ON-unaffected eyes. Results At baseline, MS patients showed lower average RNFLT ( p = 0.046) and TMV ( p = 0.013) when compared with HCs. No significant differences in the evolution of OCT measures were detected over the follow-up between MS patients and HCs. MS patients with both affected and unaffected eyes showed significantly lower average RNFLT, temporal inferior RNFLT, and TMV at baseline, compared with HCs. No significant differences between ON-affected and ON-unaffected eyes in MS patients were detected over the follow-up, except for the nasal superior RNFLT ( p = 0.019). Conclusions This study suggests a beneficial role of GA on retinal axonal degeneration in MS, and further confirms the utility of OCT to monitor the neuroprotective effect of disease-modifying treatment.